Prawo kanoniczne a państwowy porządek prawny - Pietrzak, Michał (Wydział Prawa i Administracji UAM, 1985)
A question of position of canon law of the Catholic Church in the People's Poland constitutional law is discussed in the article. The theoretical and practical impact of that issue is effected by the role and function of the Catholic Church in social and political life of the country. The study concerning Polish matters is preceeded by the synthetic presentation of the system of relations between canon law and constitutional law observed in the system of connection of State and Church and in the system of separation of Church and State. This can ensure a better presentation of Polish aspects of the issue and facilitate explanation and understanding of discrepancies caused by it. The article dwells on a problem of legal grounds of legislative autonomy of the Catholic Church in the People's Poland. It is derived by the author from the constitutionally guaranteed freedom of performing religious functions and from the principle of separation of State and Church. The author focuses on the character and scope of the autonomy. He discusses a question whether the said autonomy is of an original character — independent from acts of State or is it of a derivative character effected by the positive acts of State. The conflicts between Church and State authorities on delimiting the autonomy of the Catholic Church are also presented. Much attention is being paid by the author to explaining a problem of effectiveness of norms of canon law in the public legal order. A principle of the interindependenee of canon and public law norms is precised on the grounds of practical examples. At the same time the author indicates at the importance of knowledge of canon norms for legislative organs regulating the legal situation of the Catholic Church and also deciding issues of citizens' duties.
Canon law and the public legal order